Mobilisasi Dini sebagai Intervensi Keperawatan dalam Mencegah Komplikasi Pasien Pasca Operasi: Systematic Literature Review: Early Mobilization as a Nursing Intervention in Preventing Postoperative Complications: A Systematic Literature Review - Sucipto, Sucipto; Murtiningsih, Murtiningsih (Chakra Brahmanda Lentera Institute, 2026)
Postoperative complications remain a major problem in medical–surgical nursing care and contribute to increased morbidity, prolonged hospitalization, and higher healthcare costs. Complications such as pneumonia, deep vein thrombosis, paralytic ileus, persistent postoperative pain, and extended length of hospital stay are frequently associated with prolonged postoperative immobilization. Early mobilization has been recommended as an evidence-based nursing intervention to prevent these complications and enhance patient recovery. This study aimed to systematically review the scientific evidence on the effectiveness of early mobilization as a nursing intervention for preventing postoperative complications. A systematic literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were retrieved from PubMed, Scopus, ScienceDirect, and Google Scholar databases for publications between 2019 and 2024. The review included original research studies involving adult postoperative patients who received early mobilization interventions. The main variables reviewed were postoperative complications, including respiratory complications, venous thromboembolism, gastrointestinal dysfunction, postoperative pain, and length of hospital stay. Data were collected using outcome measurements reported in the included studies. Fifteen studies met the inclusion criteria and were included in the synthesis. The findings consistently demonstrated that early mobilization significantly reduced the incidence of respiratory complications, venous thromboembolism, and gastrointestinal dysfunction. In addition, early mobilization was associated with lower postoperative pain and a shorter hospital stay across various surgical populations. Early mobilization is an effective and evidence-based nursing intervention that plays a crucial role in preventing postoperative complications and improving patient recovery. Integrating early mobilization into standard postoperative nursing care is strongly recommended to enhance clinical outcomes and support safe, efficient recovery processes.